The translation of lexical and morphological repetitions in the Arabic novel Thartharah Fawg Alnel into the English Adrift on the Nile / Ibrahim I.I. Najjar - Najjar, Ibrahim I.I. (2014)
Repetition is an important phenomenon in Arabic-English translation. Thus, this study was carried out to examine how lexical and morphological repetitions are rendered from an Arabic literary text into English using different translation strategies. The data used in this study is derived from an Arabic novel ―Thartharah fawg alnel‖ by Naguib Mahfouz and its English translation ―Adrift on the Nile.‖ The objectives of this study are to, (i) identify the translation strategies used to render these repetitions and whether these strategies affect the quality of the original message and (ii) find out to what extent are the communicative functions of the lexical and morphological repetitions in the Arabic novel preserved or lost in the English translation. The translational strategies, as suggested by (Baker 1992), (Newmark 1988) and (Dressler and De Beaugrande 1981) together with the typology of repetitions proposed by (Dickins et al 2002) were used. Skopos theory of Reiss and Vermeer (1984) was also used. As has been noticed, the translator resorted to variation rather than repetition in his translation and that let him to use certain translation strategies, such as synonyms, near-synonyms, omission, ellipsis, paraphrase, replacement, modulation, literal translation, expansion and pronominalisation. Synonyms, near-synonyms, and omission strategies were the most common strategies used in the translation of lexical and morphological repetitions into English. As for the communicative functions of the lexical and morphological repetitions, it was found that some examples retained their functions while others lost their functions.